2022
DOI: 10.1101/2022.02.23.481594
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Theta-phase connectivity between medial prefrontal and posterior areas underlies novel instructions implementation

Abstract: Implementing novel instructions is a complex and uniquely human cognitive ability, that requires the rapid and flexible conversion of symbolic content into a format that enables the execution of the instructed behavior. Preparing to implement novel instructions, as opposed to their mere maintenance, involves the activation of the instructed motor plans, and the binding of the action information to the specific context in which this should be executed. Recent evidence and prominent computational models suggest … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 104 publications
0
1
0
Order By: Relevance
“…Synchrony in low frequencies, such as theta, is thought to underlie long-range communication between brain regions during various cognitive processes (Formica et al, 2022;Solomon et al, 2017;Canolty & Knight., 2010), including attribution of mental states and intentions. For example, Bogels and colleagues (2015) found that mentalization was associated with increased synchrony in the theta band between right TPJ and ventral mPFC.…”
Section: Introductionmentioning
confidence: 99%
“…Synchrony in low frequencies, such as theta, is thought to underlie long-range communication between brain regions during various cognitive processes (Formica et al, 2022;Solomon et al, 2017;Canolty & Knight., 2010), including attribution of mental states and intentions. For example, Bogels and colleagues (2015) found that mentalization was associated with increased synchrony in the theta band between right TPJ and ventral mPFC.…”
Section: Introductionmentioning
confidence: 99%